Extensive versus strategic reading for learning English at Khulna University, Bangladesh - Molla Nazim Uddin Ahmed; Molla Azizur Rahman; Md. Obaidullah (Studies in English Language and Education, 2018)
This article reports on a small-scale research study conducted to investigate the comparative utility of extensive reading versus strategic reading for learning English at the undergraduate level in the English Discipline at Khulna University, a public university in south-western Bangladesh. The study is based on the schema theory where background knowledge is the basis of comprehension. A pre-tested questionnaire was used to conduct a survey. Data was collected from 158 respondents, all undergraduate students in the English Department who were selected at random. The results of the study showed that strategic reading is more favorable to students compared to extensive reading for the purpose of learning ESL/EFL. Finally, the results showed that strategic reading was more effective than extensive reading for learning English. The paper concludes with a call for further large-scale studies.